2002
DOI: 10.1136/ard.61.7.617
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic load at baseline can predict radiographic disease progression in medial compartment knee osteoarthritis

Abstract: Objective: To test the hypothesis that dynamic load at baseline can predict radiographic disease progression in patients with medial compartment knee osteoarthritis (OA). Methods: During 1991-93 baseline data were collected by assessment of pain, radiography, and gait analysis in 106 patients referred to hospital with medial compartment knee OA. At the six year follow up, 74 patients were again examined to assess radiographic changes. Radiographic disease progression was defined as more than one grade narrowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

54
993
9
28

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,218 publications
(1,084 citation statements)
references
References 31 publications
54
993
9
28
Order By: Relevance
“…A nonsignificant relationship between the varus alignment and progression of OA was only found in the analysis of the K/L grade 0 -1 group in the study by Cerejo et al (10). In the study by Miyazaki et al (22), a statistically significant OR was found for the univariate analysis of varus alignment and progression of knee OA (OR 3.10, 95% CI 1.07-9.12), but not in the multivariate analysis. Cerejo et al (10) and Sharma et al (14) also investigated the relationship between valgus alignment and progression of Bruyere (42) Yes vs no (22) also investigated the association between the adduction moment and progression of OA.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…A nonsignificant relationship between the varus alignment and progression of OA was only found in the analysis of the K/L grade 0 -1 group in the study by Cerejo et al (10). In the study by Miyazaki et al (22), a statistically significant OR was found for the univariate analysis of varus alignment and progression of knee OA (OR 3.10, 95% CI 1.07-9.12), but not in the multivariate analysis. Cerejo et al (10) and Sharma et al (14) also investigated the relationship between valgus alignment and progression of Bruyere (42) Yes vs no (22) also investigated the association between the adduction moment and progression of OA.…”
Section: Resultsmentioning
confidence: 88%
“…No statistically significant relationship was found in the comparison of the middle tertile versus the lowest tertile in the group with baseline K/L grade 1 or higher or grade 2 or higher (OR 2.3, 95% CI 0.8 -6.4 and OR 1.8, 95% CI 0.4 -8.2, respectively) and in the comparison of the highest versus the lowest tertile in the group with baseline K/L grade 1 or higher. The studies by Dieppe et al (19), Miyazaki et al (22), and Spector et al (15) found no statistically significant relationship between BMI and the progression of OA. Schouten et al (37) found a significant association in the 2 highest quartiles versus the lowest quartile.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In medial knee OA with a varus malalignment, which is the most common presentation, the knee adduction angle and (externally referenced) adduction moment during gait are considered important [6,11,21,29]. The knee adduction moment is considered a surrogate of medial compartment load [1], and has been correlated with pain in medial knee OA [71], disease severity [66], and rate of disease progression [50]. However, gait analysis is not a part of routine clinical examinations of patients with knee OA.…”
Section: Introductionmentioning
confidence: 99%